(untitled) (Altre Modernità, 2018)
The political confinement was one of the instrument of persecution of the Fascist regime. This paper aims to analyze how this form of limitation of freedom, based on expulsion and isolation, political but also cultural, economic and social, has helped to overcome the concept of border. The political confinement made new relationships between the Antifascists deported and the local population. The famous novel by Carlo Levi "Christ Stopped at Eboli" describes how the men and women sent to Aliano, the town where Carlo Levi was actually imprisoned, transformed punitive experience in an encounter between different cultures, thanks to the contact with the South of Italy. What happened to Eboli, the country of Salerno mentioned in the title? Are there differences between the case of Eboli, Aliano and the South of Italy? Through the analysis of the 250 letters sent by seventy Antifascist confinemented to Eboli and Aliano, we can identify some of the main policy results, economic, cultural and social produced by Fascist political confinement in Eboli and Aliano. The historical record, made by seventy political deported, helped the renewed Italian political class to face a problem known as the "Southern question".